Upaya Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa Kelas Vii Smp Muhammadiyah 9 Yogyakarta Melalui Penerapan Pendekatan Pembelajaran Problem Posing - Martalia Ardiyaningrum (Universitas Alma Ata, 2013)
Problem-solving ability is one of the objectives to be achieved in mathematics. This capability is not only used in solving problems related to the field of mathematics, but can be used in solving the problems faced by students in the day-to-day life. One way to develop this ability in mathematics learning is learning by problem posing approach. This approach gives the opportunity for students to formulate questions that are simpler than the available problems. This research aims is to improve the ability of mathematical problem solving of students of grade VIIA, Junior High School of Muhammadiyah 9 Yogyakarta through learning â€œproblem solvingâ€. This is a classroom action research; with the subject of the research were seventh grade students of Junior High School of Muhammadiyah 9 Yogyakarta. The results of study showed that the approach can enhance the ability of posing a problem-solving mathematical, grade VII A Junior High School of Muhammadiyah 9 Yogyakarta. Keywords : Problem posing, problem solving ability